Mathematical aspects of quantum computing 2007 - Nakahara, Mikio; Rahimi, Robabeh; SaiToh, Akira (Kinki University series on quantum computing, 2008)
This book provides a comprehensive overview of the mathematical aspects of quantum computing. It will be useful for graduate students and researchers interested in quantum computing from different areas of physics, mathematics, informatics and computer science. The lecture notes in this volume are written in a self-contained style, and hence are accessible for graduate students and researchers with even less background in the topics.